TANGGUNG JAWAB PELAKU USAHA TERHADAP PENAYANGAN IKLAN NIAGA YANG MENYESATKAN KONSUMEN - Sudjana - Sudjana (Faculty of Law, Maranatha Christian University, 2021)
This study aims to determine the qualifications of misleading commercial advertisements and the responsibilities of business actors including advertisers, advertising agencies and advertising media in connection with the delivery of misleading commercial advertisements. The results showed that the provisions of Article 9 of the UUPK were included false advertising classification, fraudulent advertising types, and deceptive criteria. The provisions of Article 10 and Article 12 of the Company Law are classified as false advertising, fraudulent advertising, straight forwardlie advertising, and misleading advertising criteria. The provisions of Article 13 of the Company Law include the classification of bait and switch advertising, fraudulent advertising, straight forwardlie advertising, and misleading advertising criteria. Article 17 paragraph (1) UUPK includes the classification of false advertising, types of fraudulent advertising, and criteria for misleading and deceptive advertising. The principle of accountability of business actors according to Article 20 of the Company Law is strict liability and vicarious liability. Meanwhile, in relation to Article 9 UUPK, the forms of responsibility are product and contractual liability (Articles 10, 11, 12, 13 and 17 of the UUPK), or professional liability for advertising agencies and advertising media or both and it does not rule out the possibility of business actors being subject to sanctions. based on the principle of the presumption of liability principle and the form of responsibility for criminal liability